Analisis Daya Saing Produk Bambu Indonesia di Pasar Internasional - Vera Junita BR Sitanggang; Maria S. T. Simbolon; Bintang C. H. Simangunsong (Fakultas Pertanian, Universitas Riau, 2023)
Indonesia is the third richest country in Asia on bamboo resources. In Indonesia, bamboo has been widely used to substitute wood on many applications and also exported in certains bamboo products, such as sticks (used primarily for plaiting), charcoals, flooring, plywood, mats and screens, plaits and plaiting articles, pulp, and paper articles. This research aimed to analyse comparative and competitive advantages of Indonesian bamboo products in international market, including the factors effect its export growth on the period 2013 to 2017. Analysis was conducted under techniques RCA (Revealed Comparative Advantage), TSI (Trade Specialization Index) and CMS (Constant Market Share). Overall, the results showed that bamboo sticks and bamboo charcoals had strong and mature competitive advantages. However, bamboo flooring, bamboo plywood, bamboo mats and screens, and bamboo plaits and plaiting articles had weak competitive advantages and were on growing phase. Bamboo pulp and paper articles had had strong competitive advantages, but it was lessening to the phase of re-importing. The results of CMS analysis showed that commodity composition factor had positively affected export growth, while standard growth and competitiveness factors gave negative effect to Indonesian bamboo export growth.